When lower risk increases profit: Competition and control of a central counterparty - Jean-Sébastien Fontaine; Héctor Pérez Saiz; Joshua Slive (Bank of Canada, 2012)
We model the behavior of dealers in Over-the-Counter (OTC) derivatives markets where a small number of dealers trade with a continuum of heterogeneous clients (hedgers). Imperfect competition and (endogenous) default induce a familiar trade-off between competition and risk. Increasing the number of dealers servicing the market decreases the price paid by hedgers but lowers revenue for dealers, increasing the probability of a default. Restricting entry maximizes welfare when dealers' efficiency is high relative to their market power. A Central Counter-Party (CCP) offering novation tilts the trade-off toward more competition. Free-entry is optimal for all level of dealers' efficiency if they can constrain risk-taking by its members. In this model, dealers can choose CCP rules to restrict entry and increase their benefits. Moreover, dealers impose binding risk constraints to increase revenues at the expense of the hedgers. In other words, dealers can use risk controls to commit to a lower degree of competition. These theoretical results provide one rationalization of ongoing efforts by regulators globally to promote fair and risk-based access to CCPs.
Keywords: G10; G18; 330; Financial markets; Financial system regulation and policies; Financial stability